Moisture-absorbing, heating and odor-eliminating finishing agent as well as preparation method and application thereof

By using hygroscopic heating and odor removal finishing agents prepared by multi-vacuum adsorption materials based on metal-organic frames, the problems of poor hygroscopic heating ability and weak odor adsorption effect in the prior art are solved, and efficient warmth and odor removal are achieved Effect.

CN119433984APending Publication Date: 2025-02-14GAOMI ZHONGHE GARMENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411556586.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing functional finishing additives have poor hygroscopic heating capabilities and weak odor adsorption effects, making it difficult to meet the high-efficiency warmth and odor elimination needs of textiles.

Method used

Using multi-vacuum adsorbent material based on metal-organic frame (MOFs) structure as the main component of the finishing agent, iron-based MOF materials are prepared by hydrothermal synthesis and solvent exchange method, and combined with polyurethane adhesives and resin softeners. Form a composite functional finishing agent that absorbs moisture and heat, and eliminates odor.

Benefits of technology

It significantly improves the moisture-absorbing and heating performance and odor elimination effect of textiles, can maintain efficient performance in multiple uses, and reduces production costs and process complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005116627470000061
    Figure BDA0005116627470000061
Patent Text Reader

Abstract

The invention relates to the technical field of fabric functional finishing agents, and discloses a finishing agent capable of absorbing moisture, heating and eliminating peculiar smell as well as a preparation method and application of the finishing agent, and the finishing agent comprises the following components in parts by mass: 10-15 parts of an adsorbent, 15-20 parts of a polyurethane adhesive, 20-30 parts of a resin softening agent and the balance of water; the adsorbent is an iron-based MOF material with hydrophilicity, and MOF is a porous adsorption material with a three-dimensional network structure, wherein the porous adsorption material is obtained by assembling central Fe < 3 + > ions and organic ligands; a central Fe < 3 + > ion structure exists in the form of [Fe (OH) (COO) 2] n and [Fe3 (mu3-O) (COO) 6] clusters; the organic ligand is formed by compounding a main ligand and an auxiliary ligand, the main ligand is aromatic organic acid with a triangular plane structure, and the auxiliary ligand is at least one of bipyridine, diimidazole benzene and biphenyl with a linear structure. The finishing agent is a porous adsorption material based on the MOFs structure, has the composite functions of moisture absorption, heating and peculiar smell elimination, is fast in moisture absorption, large in moisture absorption capacity and reversible in moisture absorption process, and can be applied to functional after-finishing of textiles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional finishing agents for fabrics, and in particular to a moisture absorbing, heat generating and odor eliminating finishing agent, a preparation method thereof and applications thereof. Background Art

[0002] Hygroscopic and exothermic fabrics are a type of functional textiles that generate heat by absorbing water vapor generated by evaporation from human skin. It is generally believed that the mechanism of hygroscopic heat generation can be divided into two situations. The first is the transformation of kinetic heat energy of water molecules. The surface of hygroscopic and exothermic materials contains a large number of hydrophilic groups, which can efficiently capture water vapor on the skin surface and in the air and connect them with hydrogen bonds. In the transformation of water molecules from dynamic to static, kinetic energy is converted into thermal energy to achieve a warming effect. The second is through gas-liquid changes. While hygroscopic heat generation absorbs and fixes water molecules in the microenvironment on the surface of the human body, part of the water vapor is transformed from gas to liquid and releases heat to achieve a warming effect.

[0003] Strong water-absorbing materials include highly absorbent resins and some natural polymers. These materials generally have water-absorbing functional groups or moderately cross-linked mesh structures and have been widely used in the textile field. However, the commonly used heating matrix or load matrix does not have a porous structure, resulting in poor heat dissipation performance and low heating matrix loading rate. The moisture absorption and heating effect of the prepared finishing agent needs to be improved.

[0004] Metal-Organic Frameworks (MOFs) are organic-inorganic hybrid materials with intramolecular pores formed by self-assembly of organic ligands and metal ions or clusters through coordination bonds. Due to the wireless arrangement and combination of metal nodes and organic ligands, MOFs show unique adjustability in structure and chemical properties. Because of its highly porous structure, it shows a strong affinity for small molecules such as water and ammonia. And compared with traditional adsorption materials such as zeolite, silica gel, hygroscopic salts, it has stronger water absorption. Therefore, using MOFs materials, it is expected to develop finishing agents with hygroscopic heat generation and odor elimination, which is an important research topic in this field. Summary of the invention

[0005] The purpose of the present invention is to provide a moisture absorption and heat generation and odor elimination finishing agent to solve the problems of poor multiple moisture absorption and heat generation capacity and weak odor adsorption effect of some existing functional finishing additives, and the main component of which is a porous adsorption material based on MOFs structure. The porous adsorption material has the composite functions of moisture absorption and heat generation and odor elimination, and can be applied to the functional finishing of textiles.

[0006] To achieve the above-mentioned object, on the one hand, the present invention provides a moisture absorbing, heat generating and odor eliminating finishing agent, which comprises, by weight:

[0007] 10-15 parts of adsorbent, 15-20 parts of polyurethane adhesive, 20-30 parts of resin softener, and the balance is water;

[0008] The adsorbent is a hydrophilic iron-based MOF material, wherein the iron-based MOF material is composed of a central Fe 3+ A porous adsorption material with a three-dimensional network structure obtained by assembling ions and organic ligands;

[0009] The central Fe 3+ The ionic structure is [Fe(OH)(COO)2] n , exists in the form of [Fe3(μ3-O)(COO)6] clusters;

[0010] The organic ligand is composed of a main ligand and an auxiliary ligand. The main ligand is an aromatic organic acid with a triangular planar structure, and the auxiliary ligand is at least one of bipyridine, diimidazole benzene and biphenyl with a linear structure.

[0011] As a further preferred technical solution of the present invention, the main ligand is at least one of 2,6-di(4-carboxyphenyl)pyridine-4-carboxylic acid, 2,6-di(2,5-benzenedicarboxylic acid)pyridine, and 3,5-bipyridinebenzoic acid; and / or the auxiliary ligand is at least one of 2,2'-bipyridine, 1,4-diimidazolebenzene, and 4,4'-bipyridinebiphenyl.

[0012] According to another aspect of the present invention, the present invention also provides a method for preparing a moisture absorbing, heat generating and odor eliminating finishing agent, comprising the following steps:

[0013] S1. Using hydrated ferric sulfate as a precursor, a main ligand and an auxiliary ligand as an organic ligand, the precursor and the organic ligand are placed in an organic solvent and mixed, and the pH is adjusted to 8±0.5, and a homogeneous crystalline material is prepared by a hydrothermal synthesis method;

[0014] S2, exchanging the homogeneous crystalline material obtained in step S1 in acetone for multiple times by a solvent exchange method, and vacuum drying to obtain an adsorbent, i.e., an iron-based MOF material;

[0015] S3, mixing the adsorbent, polyurethane adhesive and resin softener in water to obtain a moisture absorbing, heat generating and odor eliminating finishing agent.

[0016] As a further preferred technical solution of the present invention, in step S1, the molar ratio of the organic ligand to ferric chloride is (3:1)-(2:1); the molar ratio of the primary ligand to the auxiliary ligand is (2:1)-(4:1). Furthermore, the primary ligand and the auxiliary ligand are added to the organic solvent according to a certain ratio, and after being fully dissolved by ultrasound, the precursor is added, and ultrasound is continued to be mixed to make them uniform.

[0017] As a further preferred technical solution of the present invention, in the hydrothermal synthesis method of step S1: the organic solvent is a mixed solvent of N,N-dimethylamide and methanol; and / or the temperature is 140-160°C, and the reaction time is at least 24 hours. Furthermore, the molar ratio of N,N-dimethylamide to methanol is 1:1.

[0018] As a further preferred technical solution of the present invention, the vacuum drying step in step S2 comprises: vacuum drying the material after solvent exchange at room temperature and 65-150° C. for 6-12 hours respectively.

[0019] As a further preferred technical solution of the present invention, in step S3, the adsorbent is first added into water to prepare an adsorbent dispersion, and then the adsorbent dispersion, polyurethane adhesive, resin softener and water are evenly mixed to obtain a moisture absorbing, heat generating and odor eliminating finishing agent.

[0020] According to another aspect of the present invention, the present invention also provides an application of a hygroscopic, heat-generating and odor-eliminating finishing agent in the preparation of a composite functional fabric, comprising: adding water to the hygroscopic, heat-generating and odor-eliminating finishing agent to prepare a working liquid; impregnating the acrylic viscose fabric with the working liquid, and then pre-baking, curing and drying the fabric to obtain the composite functional fabric.

[0021] As a further preferred technical solution of the present invention, the fabric is made of at least one of cotton, regenerated cellulose, polyester, acrylic and nylon.

[0022] As a further preferred technical solution of the present invention, the concentration of the hygroscopic and exothermic finishing agent in the working solution is 50-80 g / L.

[0023] In the present invention, the surface moisture of the fabric after padding treatment usually exists in three forms: one is free water, which can be completely desorbed when heated to about 110°C; the other is adsorbed water, which can be desorbed when heated to about 150°C; and the last is structural water, which needs to be heated to above 400°C to be desorbed. As a further preferred technical solution of the present invention, in the post-treatment of the padding fabric, the pre-baking temperature is 110-120°C, the pre-baking time is 3-5min, the curing and drying temperature is 145-160°C, and the curing and drying time is 40-90s.

[0024] As a further preferred technical solution of the present invention, the time interval between completing the preparation of the finishing agent and configuring it into a working solution is no more than 6 hours; the time interval between configuring the working solution and using the working solution is no more than 1 hour.

[0025] According to another aspect of the present invention, the present invention also provides a composite functional fabric that absorbs moisture, generates heat and eliminates odor.

[0026] The hygroscopic, heat-generating and odor-eliminating finishing agent prepared by the present invention is based on a metal organic framework, and is applied to textiles for functional finishing. Since the metal organic framework has a larger specific surface area and a higher porosity than traditional porous materials, the high porosity makes it easy for single-molecule or multi-molecular layer physical adsorption to occur, so that the pores of the material have various hydrophilic groups and hydrophilic sites, which greatly improves the affinity of the structure to water molecules and improves the hygroscopic and heat-generating effect of the fabric; the presence of high porosity not only improves the warmth retention of the hygroscopic and heat-generating fabric, but also enhances the debugging effect of the hygroscopic and heat-generating fabric, and realizes secondary or even multiple heating of the fabric; at the same time, the adsorbent has a three-dimensional multi-porous structure, combined with an ultra-large specific surface area, which can capture small molecules such as ammonia and eliminate odor.

[0027] Conventional super absorbents, although they have a strong affinity for water molecules, have poor moisture dissipation performance due to their special molecular structure, which is not conducive to multiple heating. For this reason, the present invention uses a metal organic framework as the main structure, which has a three-dimensional multi-porous structure and is connected to a hydrophilic organic ligand. On the one hand, the large specific surface area of ​​the porous material is used to enhance the moisture dissipation capacity of the hygroscopic saturated fabric in a low-humidity environment; on the other hand, the porous characteristics of the porous material are used to reduce heat loss.

[0028] Compared with the prior art, the present invention can achieve the following beneficial effects:

[0029] 1) The finishing agent of the present invention uses a metal organic framework as the main body, and adds adhesives and softeners to improve washability and hand feel, so as to serve as a moisture absorbing and heat generating functional auxiliary agent; it utilizes the characteristics of the porous topological structure of the metal organic framework to make it absorb moisture quickly, absorb a large amount of moisture, and the moisture absorption process is reversible. According to experimental statistics, the maximum temperature rise of the finished fabric within 30 minutes is 8-9°C, and after multiple washings, it can still reach a maximum temperature rise of more than 8°C, and the average temperature rise is much higher than that of the unfinished fabric;

[0030] 2) The specific surface area of ​​the adsorbent in the finishing agent of the present invention reaches 2823m 2 / g, has strong adsorption function for ammonia, isovaleric acid and 2-nonenal. In the gas chromatography deodorization performance test, the reduction rate of the three types of odor components can reach more than 80%, even up to 90%, and can still be maintained above 80% after multiple water washings;

[0031] 3) The preparation method of the finishing agent of the present invention can prepare the finishing agent without high temperature and high pressure, has high product yield, simple method, low cost, and is conducive to industrial production. DETAILED DESCRIPTION

[0032] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0033] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0034] In the following examples: the adhesive used is a polyurethane adhesive purchased from Changzhou Meisheng Biomaterial Co., Ltd., model CG-BID; the softener used is a resin softener purchased from Changzhou Meisheng Biomaterial Co., Ltd., model DCOM SOFT 35 softener; the materials of each component are calculated by weight.

[0035] Example 1

[0036] Step 1. Dissolve 4 parts of 2,6-di(4-carboxyphenyl)pyridine-4-carboxylic acid and 1 part of 2,2'-bipyridine completely in a mixed solution of 2.5 parts of N,N-dimethylamide and 2.5 parts of methanol, ultrasonically treat for 20 minutes to obtain a uniform solution, then add 2.5 parts of hydrated ferric sulfate, adjust the pH value to 8 with sodium hydroxide solution, and ultrasonicate the solution for 20 minutes. Then place the reactor in a 140°C oven and continue heating for 24 hours. After cooling and filtering, wash the solid obtained by the reaction three times with N,N-dimethylamide and methanol in turn, and dry in air. Then, the obtained homogeneous crystalline material is exchanged in acetone 8 times by solvent exchange method, each time with an interval of 4 hours, followed by vacuum drying at room temperature for 12 hours and vacuum drying at 125°C for 12 hours to obtain an adsorbent.

[0037] Step 2: Add 4 parts of the adsorbent into 96 parts of deionized water, and obtain an adsorbent dispersion by stirring-swelling-stirring operation.

[0038] Step 3: 10 parts of the adsorbent dispersion, 15 parts of the adhesive, 20 parts of the softener, and 55 parts of deionized water are mixed, and the mixture is evenly dispersed by mechanical stirring to obtain a moisture-absorbing, heat-generating, and odor-eliminating finishing agent.

[0039] Step 4: Add water to the above finishing agent to prepare a 50g / L working solution, and perform padding treatment on the (40 / 60)40S acrylic viscose fabric (the padding process is a conventional technology and is not described in detail here). After the padding is completed, pre-bake at 110°C for 3 minutes and cure at 145°C for 40 seconds to obtain a functional fabric.

[0040] Example 2

[0041] Step 1. Dissolve 3 parts of 2,6-di(2,5-benzenedicarboxylic acid)pyridine and 1 part of 1,4-diimidazole benzene completely in a mixed solution of 2.5 parts of N,N-dimethylamide and 2.5 parts of methanol, ultrasonically treat for 20 minutes to obtain a uniform solution, then add 2 parts of hydrated ferric sulfate, adjust the pH value to 8 with sodium hydroxide solution, and ultrasonicate the solution for 20 minutes. Then place the reactor in a 140°C oven and continue heating for 24 hours. After cooling, filter and wash the solid obtained by the reaction three times with N,N-dimethylamide and methanol in turn, and dry in air. The homogeneous crystalline material obtained in the above steps is exchanged in acetone 8 times by solvent exchange method, each time with an interval of 4 hours, followed by vacuum drying at room temperature for 12 hours and vacuum drying at 100°C for 12 hours to obtain an adsorbent.

[0042] Step 2: Add 4 parts of the adsorbent into 96 parts of deionized water, and obtain an adsorbent dispersion by stirring-swelling-stirring operation.

[0043] Step 3: Mix 15 parts of the adsorbent dispersion, 20 parts of the adhesive, 30 parts of the softener, and 35 parts of deionized water, and evenly disperse them by mechanical stirring to obtain a moisture-absorbing, heat-generating, and odor-eliminating finishing agent.

[0044] Step 4: Add water to the finishing agent to prepare a 80 g / L working solution, and perform padding treatment on the (40 / 60)40S acrylic viscose fabric (the padding process is the same as in Example 1). After padding, pre-bake at 120° C. for 5 min and cure at 160° C. for 90 s to finally obtain a functional fabric.

[0045] Example 3

[0046] Step 1. Dissolve 2 parts of 3,5-dipyridine benzoic acid and 1 part of 4,4'-dipyridine biphenyl completely in a mixed solution of 2.5 parts of N,N-dimethylamide and 2.5 parts of methanol, ultrasonically treat for 20 minutes to obtain a uniform solution, then add 1 part of hydrated ferric sulfate, adjust the pH value to 8 with sodium hydroxide solution, and ultrasonicate the solution for 30 minutes. Then place the reactor in a 140°C oven and continue heating for 24 hours. After cooling and filtering, wash the solid obtained by the reaction with N,N-dimethylamide and methanol three times in turn, and dry in air. The homogeneous crystalline material obtained in the above steps is exchanged in acetone 8 times by solvent exchange method, each time with an interval of 4 hours, followed by vacuum drying at room temperature for 12 hours and vacuum drying at 150°C for 12 hours to obtain an adsorbent, that is, a hydrophilic iron-based MOF material.

[0047] Step 2: Add 8 parts of adsorbent into 92 parts of deionized water, and obtain an adsorbent dispersion by stirring-swelling-stirring operation.

[0048] Step 3: 13 parts of the adsorbent dispersion, 17 parts of the adhesive, 28 parts of the softener, and 42 parts of deionized water are mixed, and the mixture is uniformly dispersed by mechanical stirring to obtain a moisture-absorbing, heat-generating, and odor-eliminating finishing agent.

[0049] Step 4: Add water to the finishing agent to prepare a 70 g / L working solution, and perform padding treatment on the (40 / 60)40S acrylic viscose fabric (the padding process is the same as in Example 1). After padding, pre-bake at 115° C. for 4 min and cure at 155° C. for 90 s to finally obtain a functional fabric.

[0050] Comparative Example 1

[0051] As a comparative experiment of Example 1, step 1 is adjusted as follows based on Example 1:

[0052] Step 1: Dissolve 4 parts of 2,6-di(4-carboxyphenyl)pyridine-4-carboxylic acid and 1 part of 2,2'-bipyridine completely in a mixed solution of 2.5 parts of N,N-dimethylamide and 2.5 parts of methanol, and stir mechanically for 20 minutes to obtain a uniform solution. Then place the reactor in a 140°C oven and continue heating for 24 hours. After cooling, filter and wash the solid obtained by the reaction with N,N-dimethylamide and methanol at least three times in sequence, and dry in air.

[0053] The experiment found that no usable solid powder was found after drying. Therefore, the comparative example 1 used an untreated fabric sample for performance testing.

[0054] Comparative Example 2

[0055] As a comparative experiment of Example 1, the following is adjusted based on Example 1:

[0056] Step 1: ultrasonically treat a mixed solution of 2.5 parts of N,N-dimethylamide and 2.5 parts of methanol for 20 minutes to obtain a uniform solution, and then add 2.5 parts of hydrated ferric sulfate and ultrasonicate for 20 minutes. Then place the reactor in a 140°C oven and continue heating for 24 hours. After cooling, filter and wash the solid obtained by the reaction with N,N-dimethylamide and methanol at least three times in sequence, and dry in air. And vacuum dry at room temperature for 12 hours and at 125°C for 12 hours to obtain a dry solid.

[0057] Step 2: Add 4 parts of dry solid to 96 parts of deionized water, and obtain a dispersion by stirring-swelling-stirring operation.

[0058] Step 3: Mix 10 parts of the dispersion, 15 parts of the adhesive, 20 parts of the softener, and 55 parts of deionized water, and evenly disperse them by mechanical stirring to obtain a finishing agent.

[0059] Step 4: Add water to the finishing agent to prepare a 50 g / L working solution, and perform padding treatment on the (40 / 60)40S acrylic viscose fabric (the padding process is the same as that in Example 1). Then pre-bake at 110° C. for 3 min and cure at 145° C. for 40 s to obtain a functional fabric.

[0060] The fabric samples of the above-mentioned Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests according to the following standards:

[0061] The finished fabrics were washed 50 times with reference to the standard GB / T 8629-2017 "Household washing and drying procedures for textile testing".

[0062] The moisture absorption and heat generation performance of fabrics before and after washing was tested according to the method in the reference standard GB / T 29866-2013 "Textiles - Test Method for Hygroscopic and Heat Generation Performance". The test conditions are temperature 20℃, humidity 90%, test time 30min, and the average temperature rise value and the maximum temperature rise value of the test sample within 30min are recorded.

[0063] The deodorizing performance of ammonia, isovaleric acid and 2-nonenal was tested on the fabrics before and after the washing test in accordance with the reference standard GB / T 33610.3-2019 "Determination of deodorizing performance of textiles Part 3: Gas chromatography". The test conditions are that the sample is in contact with the odor solution for 2 hours, the sampling needle is inserted to a height of 4 cm, and the gas concentration is calibrated using gas chromatography.

[0064] Table 1 shows the test results of moisture absorption and heat generation and deodorization performance of Examples 1-3 and Comparative Examples 1-2, wherein the maximum temperature rise of the fabric within 30 minutes is recorded as ΔTmax, and the average temperature rise is recorded as ΔTaverage.

[0065] Table 1. Test results of moisture absorption, heat generation and deodorization performance of Examples 1-3 and Comparative Examples 1-2

[0066]

[0067] By comparing the data in Table 1, it can be seen that the overall hygroscopic and heat-generating performance and deodorizing performance of the embodiment are significantly improved compared with the comparative example. The hygroscopic and heat-generating and odor-eliminating composite finishing agent prepared by this patent can significantly improve the hygroscopic and heat-generating performance and deodorizing performance of the fabric, and has good functional durability after finishing.

[0068] Comparative Examples 1 and 2 are both comparative samples prepared based on Example 1. From the analysis of the results in Table 1, it can be seen that the precursor (Comparative Example 1) and the organic ligand (Comparative Example 2) have an important influence on the preparation of the adsorbent, thereby affecting the application performance.

[0069] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A moisture absorbing, heat generating and odor eliminating finishing agent, characterized in that: Calculated by mass, including: 10-15 parts of adsorbent, 15-20 parts of polyurethane adhesive, 20-30 parts of resin softener, and the balance is water; The adsorbent is a hydrophilic iron-based MOF material, wherein the iron-based MOF material is composed of a central Fe 3+ A porous adsorption material with a three-dimensional network structure obtained by assembling ions and organic ligands; The central Fe 3+ The ionic structure is [Fe(OH)(COO)2] n , exists in the form of [Fe3(μ3-O)(COO)6] clusters; The organic ligand is composed of a main ligand and an auxiliary ligand. The main ligand is an aromatic organic acid with a triangular planar structure, and the auxiliary ligand is at least one of bipyridine, diimidazole benzene and biphenyl with a linear structure.

2. The moisture absorbing heat generating and odor eliminating finishing agent according to claim 1, characterized in that: The main ligand is at least one of 2,6-di(4-carboxyphenyl)pyridine-4-carboxylic acid, 2,6-di(2,5-benzenedicarboxylic acid)pyridine, and 3,5-dipyridinebenzoic acid; And / or, the auxiliary ligand is at least one of 2,2'-bipyridine, 1,4-diimidazole benzene, and 4,4'-bipyridine biphenyl.

3. The method for preparing the moisture-absorbing heat-generating and odor-eliminating finishing agent according to claim 1 or 2, characterized in that: The following steps are involved: S1. Using hydrated ferric sulfate as a precursor, a main ligand and an auxiliary ligand as an organic ligand, the precursor and the organic ligand are placed in an organic solvent and mixed, and the pH is adjusted to 8±0.5, and a homogeneous crystalline material is prepared by a hydrothermal synthesis method; S2, exchanging the homogeneous crystalline material obtained in step S1 in acetone for multiple times by a solvent exchange method, and vacuum drying to obtain an adsorbent, i.e., an iron-based MOF material; S3, mixing the adsorbent, polyurethane adhesive and resin softener in water to obtain a moisture absorbing, heat generating and odor eliminating finishing agent.

4. The method for preparing the moisture-absorbing, heat-generating and odor-eliminating finishing agent according to claim 3, characterized in that: In step S1, the molar ratio of the organic ligand to the precursor is (3:1)-(2:1); the molar ratio of the primary ligand to the auxiliary ligand is (2:1)-(4:1).

5. The method for preparing the moisture-absorbing heat-generating and odor-eliminating finishing agent according to claim 3, characterized in that: In the hydrothermal synthesis method of step S1: the organic solvent is a mixed solvent of N,N-dimethylamide and methanol; and / or the temperature is 140-160° C., and the reaction time is at least 24 hours.

6. The method for preparing the moisture-absorbing, heat-generating and odor-eliminating finishing agent according to claim 3, characterized in that: The vacuum drying step in step S2 includes: The solvent exchanged material was vacuum dried at room temperature and 65-150°C for 6-12 hours respectively.

7. Use of a moisture absorbing, heat generating and odor eliminating finishing agent in the preparation of composite functional fabrics, characterized in that: The moisture-absorbing, heat-generating and odor-eliminating finishing agent of claim 1 or 2 is added with water to prepare a working liquid; the fabric is impregnated with the working liquid, and then pre-baked, cured and dried to obtain a composite functional fabric.

8. The use according to claim 7, characterized in that: The fabric is made of at least one of cotton, regenerated cellulose, polyester, acrylic and nylon.

9. The use according to claim 7, characterized in that: The concentration of the hygroscopic and exothermic finishing agent in the working solution is 50-80 g / L.

10. The use according to claim 7, characterized in that: The pre-baking temperature is 110-120°C, the pre-baking time is 3-5 minutes, the curing and drying temperature is 145-160°C, and the curing and drying time is 40-90 seconds.